2015
DOI: 10.1111/hdi.12307
|View full text |Cite
|
Sign up to set email alerts
|

The effect of hemodialysis session on postural strategies in older end‐stage renal disease patients

Abstract: Patients suffering from end-stage renal disease experience multiple disabilities, such as muscle wasting, weakness, higher postural sway, and fall rates compared with healthy population, which has a negative effect on physical functioning and autonomy. The vital treatment of hemodialysis is recognized to induce important post-hemodialysis fatigue, hypotension, cramps, and headache due to the rapid fluid redistribution, among others. Nevertheless, even the well-known negative effect of aforementioned consequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
7
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 34 publications
3
7
0
3
Order By: Relevance
“…The GN patients have higher postural sway and therefore potentially higher risk of falls with consequent morbidity and disability. 18 Finally, the increase in both physical (+72%) and mental dimensions (+40%) of QoL observed in GN-Ex is consistent with Painter's study, 17 which demonstrated that the frailest patients experienced the greatest improvement in QoL following exercise. The QoL scores are highly predictive of hospitalizations and mortality 19 ; thus, the improvement obtained in GN-Ex patients is even more interesting, satisfactory, and fully positive, given the specific characteristics of the studied population.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The GN patients have higher postural sway and therefore potentially higher risk of falls with consequent morbidity and disability. 18 Finally, the increase in both physical (+72%) and mental dimensions (+40%) of QoL observed in GN-Ex is consistent with Painter's study, 17 which demonstrated that the frailest patients experienced the greatest improvement in QoL following exercise. The QoL scores are highly predictive of hospitalizations and mortality 19 ; thus, the improvement obtained in GN-Ex patients is even more interesting, satisfactory, and fully positive, given the specific characteristics of the studied population.…”
Section: Discussionsupporting
confidence: 83%
“…The balance assessment reinforced this key point. The G N patients have higher postural sway and therefore potentially higher risk of falls with consequent morbidity and disability . Finally, the increase in both physical (+72%) and mental dimensions (+40%) of QoL observed in G N‐Ex is consistent with Painter's study, which demonstrated that the frailest patients experienced the greatest improvement in QoL following exercise.…”
Section: Discussionsupporting
confidence: 83%
“…Furthermore, a greater postural sway in the post-versus pre-HD session was observed [18] in addition to poorer postural control in HD patients than in age-matched controls, which was further exacerbated by the simultaneous performance of a cognitive task [19]. These results suggest that the immediate post-HD period is particularly unsafe, so medical staff in dialysis units should be sure to provide the necessary support [18]. Accordingly, dialysis staff should consider such alterations concerning physical function post-dialysis as well as the probability of the aforementioned postural hypotension immediately after the HD session.…”
Section: Discussionmentioning
confidence: 86%
“…Soangra et al reported decreased sit-to-walk test performance pre-versus post-HD session [17]. Furthermore, a greater postural sway in the post-versus pre-HD session was observed [18] in addition to poorer postural control in HD patients than in age-matched controls, which was further exacerbated by the simultaneous performance of a cognitive task [19]. These results suggest that the immediate post-HD period is particularly unsafe, so medical staff in dialysis units should be sure to provide the necessary support [18].…”
Section: Discussionmentioning
confidence: 96%
“…In a small study of twelve patients it was noted that an HD session had a negative impact on postural balance, however there was no evaluation of an HD specific risk factor for the worsening balance. 22 Our study evaluated the relationship with intra-dialytic hemodynamics (an HD specific risk factor) and changes in mobility post HD. Our results suggest that greater drop in BP during dialysis, even in the absence of absolute hypotension (SBP < 100), can lead to impairment in gait speed adds important information on HD specific risk factors for functional impairment post HD.…”
Section: Discussionmentioning
confidence: 99%